Comparative Analysis of Quantity Take-Off Conventional Methods with Bim-Based Calculations in Bridge Concrete Structure Work: Case Study: Rengat-Pekanbaru Section of the Trans Sumatra Toll Road Project - Stefanus, Stefanus; Lutfiansyah, Yopi (Jurnal Teknik Sipil, 2025)
development. Generally, QTO work is carried out using conventional methods, namely by calculating the dimensions of building elements through area, volume and length. Revit is BIM-based software released by Autodesk which can be used to calculate QTO in a construction project. In this research, a comparison was made of the QTO calculations for concrete structures for bridges from the Rengat-Pekanbaru Toll Road Construction Project at STA 172+684.110 using conventional methods and BIM methods. 3D modelling was carried out with the help of Autodesk Revit software, while conventional calculations were carried out by calculating the volume based on the Initial Stage Plan Drawing (RTA) with the help of Autocad software. There is a deviation or difference in the output results of the QTO calculation of the bridge concrete spun pile work 1.64%, Diaphragm 0.25%, barrier 1.91%, abutment 0.69%, tread plate 3.64%, Pilecap 0.33%, Pier 0.13%, and Pier Head 0 .74%. According to BIM experts, the tolerance for QTO calculation deviation is 0-5%, if it is more than the limit then a recalculation must be carried out. One of the causes of calculation deviation is due to human error.